VISUAL ART AS A TOOL TO LEARN ABOUT LITERATURE - Clara Ling Boon Ing; Che Aleha Ladin; Lim Jia Wei (UUM Press, 2024)
Purpose - Art forms such as music and drama are among some recognised tools used by educators. This has sparked interest in how art can be used in education, making it a fertile field for educational research. However, there is a missing connection in how drawing can be used as a tool for English as a Foreign Language (EFL) students to learn about literature. Methodology - This paper will incorporate an Arts-Based Research (ABR) method to determine how visual art, particularly drawing, can be used as a tool to advance EFL students' understanding of a selected literary text, Edgar Allan Poe's "The Tell-Tale Heart" (2015) This qualitative study, viewed through the lens of Richard Mayer's Cognitive Theory of Multimedia Learning (CTML), involved 10 EFL participants and revealed strategies for integrating drawing that are absent in traditional approaches. Additionally, Hameed's (2022) elements of art, Yenawine's (2014) Visual Thinking Strategies (VTS), and Showalter's (2003) concepts of literature learning will be included to ground the framework of the intervention. Findings - This study can be regarded as a method to liberate traditional teaching practices into contemporary approaches, serving as a tool to merge cultural knowledge while improving confidence, higher-order thinking skills, and expression. It also allows educators to be flexible and provoke more reflection and participation. The data discusses three main strategies in exploring how integrating drawing can help EFL students learn about literature: mining to trigger thoughts, engaging with the senses, and giving permission to wonder. Visual art allows individuals to create their responses by exploring new ideas and representing emotions, confirming plans, and comprehending the deeper level of literary texts. Significance - The study will offer insight and work as an alternate strategy for educators and learners alike to utilise visual art as a tool in teaching and learning literature. The findings will also ease the alarming condition where literature teaching and learning are stereotyped as daunting.